2001
DOI: 10.1103/physrevd.64.052002
|View full text |Cite
|
Sign up to set email alerts
|

Improved measurement of thed¯/ūasymmetry in the nucleon sea

Abstract: Measurements of the ratio of Drell-Yan yields from an 800 GeV/c proton beam incident on liquid hydrogen and deuterium targets are reported. Approximately 360,000 Drell-Yan muon pairs remained after all cuts on the data. ¿From these data, the ratio of anti-down (d) to anti-up (ū) quark distributions in the proton sea is determined over a wide range in Bjorken-x. These results confirm previous measurements by E866 and extend them to lower x. From these data, (d −ū) and (d −ū)dx are evaluated for 0.015 < x < 0.35… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
272
2
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 399 publications
(287 citation statements)
references
References 73 publications
12
272
2
1
Order By: Relevance
“…One further cross-check of the robustness of the present result is performed. For the CSKK fit,d −ū at x ∼ 0.1 is negative, approximately 2-3 standard deviations away from the positive value suggested by the E866 fixedtarget Drell-Yan data [17]. It has been suggested that if positive (d −ū) were imposed on the fit [16], the strangeness would decrease since largerd is correlated to smaller strangeness in the current parametrization.…”
Section: Resultsmentioning
confidence: 78%
See 1 more Smart Citation
“…One further cross-check of the robustness of the present result is performed. For the CSKK fit,d −ū at x ∼ 0.1 is negative, approximately 2-3 standard deviations away from the positive value suggested by the E866 fixedtarget Drell-Yan data [17]. It has been suggested that if positive (d −ū) were imposed on the fit [16], the strangeness would decrease since largerd is correlated to smaller strangeness in the current parametrization.…”
Section: Resultsmentioning
confidence: 78%
“…Thus it seems that the collider data do favor a larger strangeness ratio than neutrino di-muon data. The ABM group [16] has made a study which focuses on the potential incompatibility of a large strangeness ratio with the positive value ofd −ū at x ∼ 0.1 observed by E866 [17]. This is addressed at the end of Sec.…”
Section: Introductionmentioning
confidence: 99%
“…Drell-Yan experiments [17,18] have measured a large asymmetry in this x range, and precision measurements of R W at RHIC can provide independent constraints on the flavor asymmetry which are free from the assumption of charge symmetry required in Drell-Yan. Measurements of the lepton charge asymmetry at the LHC [33,34] provide similar constraints on the quark and antiquark PDFs, though at significantly lower x due to the much higher energy of the collisions.…”
Section: The W Cross Section Ratiomentioning
confidence: 99%
“…Comparable distributions for the antiquarks within the proton sea, however, are much more weakly constrained. Interest in these poorly-known antiquark PDF's has also increased over the last few years, due to results from Drell-Yan experiments [17,18] which find evidence for a much largerd/ū flavor asymmetry in the nucleon than had been anticipated, especially at momentum fractions near and above x ∼ 0.2. Detailed measurements of W ± and Z/γ * production in proton-proton collisions will provide new and complementary information about this flavor asymmetry in the sea, from different reactions and at very different momentum scales.…”
Section: Introductionmentioning
confidence: 99%
“…ZEUS HERA-II DIS cross-sections [33,34]; CHORUS inclusive neutrino DIS [35], and NuTeV dimuon production data [36,37]; fixed-target E605 [38] and E866 [39][40][41] DrellYan production data; CDF W asymmetry [42] and CDF [43] and D0 [44] Z rapidity distributions; CDF [45] and D0 [46] Run-II one-jet inclusive cross-sections; ATLAS [47], CMS [48] and LHCb [49] data on vector boson production; and ATLAS one-jet inclusive cross-sections [50] from the 2010 run. In NNPDF3.0, several new datasets have been included.…”
Section: Jhep04(2015)040mentioning
confidence: 99%